دور تقانة المعلومات و الاتصالات في تحقيق المزايا التنافسية : دراسة استطلاعية في الشركة العامة لصناعة الادوية و المستلزمات الطبيةنينوى - د. محمد عبدالوهاب العزاوي; د. احمد سليمان محمد الجرجري (PROSPECTIVE RESEARCHES, 2023)
This research aims at studying the relationship between communication & information technology & competitive advantages. So availability of this technology in organizations is one of the competitive advantages achieving requirement. This relation has been tested according to data analysis results which are collected by questionnair which deleverd on a sample includes (47) of depts &units heads in the general company for drugs industry & medical appliances in Nineveh. The results show significant effect &correlation relationship between communication & information technology & competitive advantages due to their components & dimintions. So it leads us to conclude that competitive advantages get their achieving principles from communication & information technology components. Finally, the research has provided some suggestions.